Mercury in a Sieve: a Search for Meaning in the Responses of Prospective Teachers - Barbara G. Pace; Jane S. Townsend; Susan Nelson Wood (Networks: An Online Journal for Teacher Research, 2002)
Investigative, inquiry projects are frequently used in teacher education programs to help prospective teachers develop as critically responsive practitioners who respond to diversity. In this article we examine our effort to explore the influence of these projects. As we trace our exploration of data gathered from respondents, 90% of whom were white women, we disclose how relational priorities surfaced in the data, how these priorities complicated our readings, and how they led us to consider gender and relationship in the lives of the participants. We raise questions about the process that might be used to understand what preservice teachers are learning as they engage in inquiry projects and how we might determine the effectiveness of these projects in teacher education classes.